Motivation and its impact on organization - Dhaliwal, Amrita (International Journal of Scientific Research and Management (IJSRM), 2016)
Motivation is an internal feeling which can be understood only by manager since he is in close contact with the employees. Needs, wants and desires are inter-related and they are the driving force to act. These needs can be understood by the manager and he can frame motivation plans accordingly. We can say that motivation therefore is a continuous process since motivation process is based on needs which are unlimited. Motivation is important to an individual as it will help him to achieve his personal goals. If an individual is motivated, he will have job satisfaction . Motivation is important to a business as the more motivated the employees are, the more empowered the team is. The more is the team work and individual employee contribution, more profitable and successful is the business. Motivation will lead to an optimistic and challenging attitude at work place.